CD3+ Tumor Infiltrating Lymphocytes (TILs) in Gastric Adenocarcinoma (Mugda Medical College Journal, 2026)
Gastric cancer is the fifth most common cancer worldwide. Early and proper diagnosis and proper assessment of prognosis is one of the most important things for treatment response. The presence and activity of tumor-infiltrating lymphocytes (TILs) is a key parameter related to the antitumor immune response. The role of CD3+ TIL as a prognostic marker as well as the role in targeted immunotherapy has been studied in many cancers including adenocarcinoma of the stomach. A cross-sectional study was conducted in the Department of Pathology, Sir Salimullah Medical College, Dhaka, Bangladesh, from March 2022 to February 2024, to evaluate the expression of CD3+ tumor infiltrating lymphocytes in gastric adenocarcinoma and their association with histological grade and pathological stage. This. A total of 50 gastrectomy samples with histopathologically confirmed diagnosis of gastric adenocarcinoma were included in this study. The expression of CD3+ in TILs were evaluated in formalin-fixed and paraffin embedded specimens by immunohistochemistry. The CD3+ TILs were categorized as positive and negative expressions. The mean age of the participants was 54.98±12.10 years. Most of the tumors were located in the lesser curvature (34%), while most of the tumors were intestinal type (60%). On staging of tumors, 52% cases were in stage T3, followed by stage T1 (22%), stage T2 (14%) and stage T4 (12%). CD3+ intratumoral and stromal TIL expression was positive in 34(68%) and 28(56%) cases respectively. Significant association was found between intratumoral CD3+ TILs and tumor grade, pathological stage and nodal status (p0.05). As part of tumor microenvironment, CD3+ TIL influence the progression and differentiation of gastric adenocarcinoma. These expression levels can be utilized as indicators of biological behavior and prognosis as well as in therapeutic purpose of gastric adenocarcinoma.Mugda Med Coll J. 2026; 9(1): 18-24